DEVELOPMENT OF PHYSICOTECHNOLOGICAL BASIS OF UNCONVENTIONAL ENERGY SOURCES IN TEACHING THE DEPARTMENT OF ELECTROMAGNETISM ON THE BASE OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES - Ismailov Batir Berdiyarovish (International Scientific and Current Research Conferences, 2022)
The article describes the systematic and structured visual study methodology of the main processes and phenomena of the "Electricity and Magnetism" department of physics.